PENGABDIAN KEPADA MASYARAKAT DENGAN JUDUL PELATIHAN BERBICARA PRODUKTIF PADA MASYARAKAT NAULI BULUNG DESA PARINGGONAN - Sari Tanjung, Delima (CV. Alfa Pustaka, 2024)
Productive speaking training is a community service activity that aims to improve public speaking skills in the community of Nauli Bulung, Paringgonan Village. This training was carried out with a persuasive communication theory approach which includes three main elements: ethos, pathos, and logos. This activity is designed to help the community in speaking confidently, organizing ideas clearly, and conveying messages persuasively. The methods used in the training include providing theoretical materials, speaking simulations, and feedback evaluations. The results of the training showed a significant increase in self-confidence, the ability to organize ideas, and the use of persuasive speaking techniques. Most of the participants felt more prepared to speak in public and were able to apply the speaking skills they had learned. This training makes a positive contribution to the development of communication skills of the Paringgonan Village community.